The Development of the ‘hry(w) wdb(w)’ Beginning in the Archaic Period - Metawi, Rasha.
The present paper is concerned with the title Hry wDb  and its holders during the Old and Middle Kingdom. The title’s earliest attestations date from the Early Dynastic period, yet most of its holders lived during the Fourth and Fifth Dynasties. It enjoyed the greatest popularity during the Fifth Dynasty. The title has always deserved attention, as one of those frequently incorporated into the titularies of officials related to the king or his palace. Its meaning has been debated by a number of scholars, as has the function assigned to its holders, nevertheless, it remains uncertain. After discussing the various scholarly interpretations of the title Hry wDb , the present study examines as many of its attestations as possible, in order to establish its inherent meanings, the nature of activities assigned to its holders, and to trace the development of their institution, the “pr ?ry w?bw. ”